SOSIALISASI PARENTING DALAM UPAYA MENINGKATKAN PEMAHAMAN PERAN ORANG TUA TERHADAP PERKEMBANGAN SOCIAL EMOSIONAL ANAK - Rr. Agung Kesna Mahatmaharti; Siti Dinarti (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2024)
This parenting socialization aims to increase understanding of the role of parents towards children's social emotional development. In today's digital era, the role of parents is very important in shaping the character and social emotional abilities of children from an early age. This activity was carried out at TK Muslimat IV Nidhomiyah Jombang with the subject of student guardians. The method used in the implementation of this service activity is in the form of socialization designed to provide parents with knowledge and practical skills in supporting their child's social emotional development. Through this activity, it can increase parents' understanding of the importance of effective communication, empathy, and emotional support in forming socially and emotionally healthy children. The follow-up of this community service activity is expected to improve the quality of relationships between parents and children, as well as create a more harmonious and supportive family environment.